ANALYSIS OF LEARNER’S CONJECTURE ABILITY IN SOLVING OPEN-ENDED PROBLEMS - Lupita Wulandari; Rooselyna Ekawati (MATHEdunesa, 2022)
Conjecture will always be used by learners in problem solving, because the conjecture itself is tied to activities such as logical reasoning, translating problems, analyzing and evaluating an information to obtain valid decisions related to problem solving, where the conjecture is also able to develop the learning process of the learner in making a statement, especially with the help of open problems in its application, Which can make learners morecreative. This research aims to illustrate the conjecture ability of learners in open-ended problems with descriptive types of research and qualitative approaches to number pattern material, especially generalizing patterns. The subjects of the study are four learners who have a high and moderate level of mathematical ability and are willing to take part in interviews. The results showed that all subjects have not been able to perform every stage on constructing the conjecture, especially in the stage of arguing the conjecture and there is one subject who does not do the stage of proof of the conjecture because it is confident in the formula that has been given by the teacher. So that learning activities are needed in which there is problem solving that collects the ability of learners' contours, open-ended problems can also be one of the problem choices that can help students build their thought processes independently, and not bound by the formula of teachers or books.